Semantic Change of Arabic Nouns in the al-Qur’ān: Form, Process and Social Impact l Tagyīr al-Ma’nā min Kalimah Ism al-Lugah al-’Arābiyyah fī al-Qur’ān: al-Syakl wa al-‘Amaliyyah wa al-Âŝar al-Ijtimā’iyyah - Najib, Aan; Malik, Ahmad Abdul (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
This study discusses the semantic change of Arabic nouns in the Al-Qur'an: the form, process, and social impact. The theory used in this research is socio-semantic, which is a combination of sociology and semantics. When the absorption form is analyzed, a comparison of the original form with the absorption form is used. In this research, some Arabic nouns in Al-Qur'an that have semantic change are found, such as isim ma'rifah, nākirah, mudzakkar, muannats, masdār, mufrād, mutsanna ,jama’ etc. Semantic change occurs due to the linguistic factors surrounding them, including phonetic, syntactic and morphological; or non-linguist factors including the history of language, aspects of social culture, aspects of science and technology, aspects of foreign languages, aspects of differences in the usage, and aspects of psychological. The change of its meaning has a positive impact on people's mindsets and understanding of the study of Al-Qur'an in a comprehensive and integrated way. Then,  every word is not only understood  by its literal meaning, but also its multi-meaning.